INFORMATION AND COMMUNICATION TECHNOLOGIES DURING THE ORGANIZATION OF INDIVIDUAL WORK ON FOREIGN LANGUAGE LESSONS - Dolynskyi, Yevhen V. (Educological discourse, 2015)
The article deals with the procedure of seniour pupils individual work in specialized schools at foreign language lessons with ICT (information-communication technologies). The concept of seniour pupils individual work is determined, the methodical description of the possibilities of using information and communication technologies in the process of individual work in specialized schools at foreign language lessons are caracterized.